Growing black pepper high-tech way - Anandaraj, M; Kandiannan, K; Prasath, D (Indian Horticulture, 2019)
Traditionally, ground runners produced from basal nodes of disease-free, stable yielding black pepper plant are collected after pre-monsoon showers and planted directly in field at a distance of 30 cm away from the support. In some countries, farmers use top shoots (orthotrope) for establishing plantation as it has advantage of producing lateral branch from basal portion of support. The success of establishment of directly field planted cuttings depends on prevailing climatic conditions. The success rate of establishment in the main field can be enhanced by planting rooted cuttings. For which, runners are cut into two or three node cuttings and kept for rooting in the nursery. On its establishment, rooted cuttings are transplanted in the main field. In traditional method, only limited numbers of cutting could be made and success rate is less. The sprouting success can be increased by treating it with growth hormones and keeping in low cost humid chambers.